Historia kultury jako samodzielna dyscyplina badań historycznych a cywilizacyjne koncepcje Feliksa Konecznego - Kolbuszewska, Jolanta (Acta Universitatis Lodziensis. Folia Historica, 2003)
The aim of this article is to give a brief profile of the reorientation in Polish historiography in the latest 19th and the beginning of 20th century. During the process of modernisation the methodological vision of historical science has changed. Traditional academic historiography concentrated on political and diplomatic events lost significance in value. Apart from economic history a history of culture has become increasingly one of the most popular area of interest. In the first part of this article I tried to show how the history of culture gained independancy among the other discipline existing in 19th century Polish historical knowledge. In the second part I tried to reconstruct the reflection of civilisation of Feliks Koneczny who is still less known as a historian. I located his considerations on the ground of history of culture. As a result the article demonstrates how Koneczny’s research practice and his theoretical conceptions break away from tradition and transcend the level of its contemporary theoretical experience.